Diagnóstico de los manglares de Veracruz: distribución, vínculo con los recursos pesqueros y su problemática - Moreno Casasola, Patricia; Rojas Galaviz, José Luis; Zárate Lomelí, David; Ortiz Pérez, Mario Arturo; Lara Domínguez, Ana Laura; Saavedra Vázquez, Teresa (Instituto de Ecología, A.C., 2016)
The mangrove area of the coast of the State of Veracruz is determined from 28 maps of land use and vegetation from the INEGI, (1:50 000), and the interpretation of aerial photographies of the land use (1:75 000 and 1:80 000). The distribution of the mangroves is analyzed with emphasis on the hydrological aspects and coastal geomorphology, because they represent the main environmental forcing functions that determine the magnitude and persistence of the coastal primary producers. The relationship among commercial capture of fishing resources and the mangrove areas, watershed area and fluvial discharge identified in the veracruzan coast is analyzed by regression. The watershed area presents significant positive correlation (0.9960 prob. 0.0040). This determines that the fishing captures do not depend exclusively of one factor rather they are the ecological consequence of more complex coastal processes. The pollution sources and environmental impacts due to urban growth determine the mangrove distribution and abundance in the Veracruz coastal zone. Therefore, it will be necessary to establish the management options of protection and conservation under the present legislation. The mangrove areas analysis surpasses the exclusive environmental location, and it is necessary an integral analysis of their problem to better understand the effects and the causes that determine them.